Sea clutter characterisation & small target detection in maritime surveillance radar - Chidambaram, Nadaraj (2005)
Maritime surveillance radar experiences serious limitations imposed on their performance by unwanted sea clutter. Sea clutter limits the performance of the radar, so it is vital to understand the characteristics of sea clutter to improve the performance in detecting small targets. A detail analysis of experimental live recorded radar data collected at Port Hanstholm, Denmark with Terma Scanter X band Radar was used to test the theoretical and experimental models developed by many researches on sea clutter. The amplitude video voltage of collected digitized raw video consisting of targets and clutter of each radar sweep were measured and analyzed. The histogram from the collected samples of echo returns were plotted, a comparison of the amplitude histograms with Gaussian and Rayleigh distributions were done. The analysis of the recorded amplitude histogram has demonstrated for high resolution with low grazing angle and using horizontal polarization the data distribution fits the log normal distribution. The study concludes the statistics of sea clutter vary with polarization, resolution cell size, sea state and wind conditions.